Analysis of Inverse Positional and Workspace of a Novel 2-RPU/UPU Parallel Mechanism - Li Hong; Hu Yang; Li Ruiqin; Li Xuexian; Li Junshuai (Jixie chuandong)
According to the structure and layout of less DOF 2-RPU/UPU parallel mechanism,it is overconstraint. The 3-dimensional model of the mechanism is established in Pro/E. By using the screw theory,the DOF analysis of freedom of this mechanism is carried out. The inverse position solution is obtained by mechanism space coordinate transformation. Finally,the workspace of this parallel mechanism is solved by using Simmechanics toolbox in MATLAB.